Corporate sustainability assessments: A systematic literature review and conceptual framework. (1st May 2021) - Pranugrahaning, Agnes; Donovan, Jerome D.; Topple, Cheree; Masli, Eryadi K.
Abstract: Over the past several decades, an increasing series of global initiatives have been launched to direct the transition of businesses towards addressing sustainability. Corporate sustainability assessments have been identified as a process that can support businesses transitioning towards addressing sustainability, yet the field remains largely fragmented. This study aims to consolidate the corporate sustainability and corporate sustainability assessment literature, presenting a corporate sustainability assessment conceptual framework. A specific focus is on identifying the processes for corporate sustainability assessments implemented businesses to address the identified gap in the corporate sustainability literature on how managers are addressing sustainability through their systems and processes. A multistage systematic literature review of articles on corporate sustainability and corporate sustainability assessments that focus on a managerial perspective is performed. Drawing from the analytical review undertaken, a conceptual framework for corporate sustainability assessment is proposed. The proposed framework provides clearer guidance for businesses in addressing sustainability issues within business activities. The review and subsequent presentation of a conceptual framework consolidates the existing knowledge and practice from the corporate sustainability and corporate sustainability assessment research domains. Highlights: Corporate sustainability assessments guide managers in addressing sustainability. A systematic literature review is undertaken to map knowledge foundations. A conceptual framework is developed to provide clearer guidance to managers.